Efektivitas Pertemuan Tim Multidisiplin dalam Meningkatkan Outcome Tata Laksana Kanker di Rumah Sakit: Literature Review - Ganapati, Ngakan Putu Daksa; Sulistiadi, Wahyu (UI Scholars Hub, 2026)
Optimal cancer management requires a multidisciplinary approach to improve the quality of patient care. Multidisciplinary teams (MDTs) enable interprofessional collaboration in designing comprehensive, patient-centered care. However, the implementation of MDTs in Indonesia still faces various challenges, necessitating a systematic review to understand their effectiveness in improving cancer management outcomes. This systematic review employed the PRISMA method, searching articles from the ScienceDirect, Semantic Scholar, and PubMed databases, published between 2014 and 2024. Ten scientific articles were analyzed from 745 articles retrieved to understand the effectiveness of MDTs in improving cancer management outcomes. The results indicate that MDTs improve the quality of clinical decisions, expedite diagnosis, and increase adherence to treatment protocols. MDTs also reduce postoperative complications and improve patients' quality of life through a more holistic approach. However, limitations such as resource constraints, decision fatigue, and communication challenges can hinder their effectiveness. MDTs improve the quality of clinical decisions, expedite diagnosis, and optimize patient care plans by holistically considering medical, psychosocial, and nutritional needs. Therefore, the development and implementation of more effective MDTs are crucial to ensure equitable access and quality of cancer care.